Flood Disaster Risks to Resilient: Sustainability of Kathmandu Valley - Karki, Parbata Devi (Rural Development Journal, 2025)
Kathmandu valley is the flat land surrounded by hills in a bowl shape. Surrounding hill is the origin of Bagmati River in Bagdwar and its tributaries. The sustainability of Kathmandu valley depends on the protection of the civilization of Bagmati River basin and the natural environment. This is the key to resilient. The aim of this study is to explore multifarious effects of floods in Kathmandu valley and to analyze the effort towards resilience. This is the crucial issue of its sustainability. The qualitative and quantitative data of secondary source have been used to explain the scenario of floods, status of resilient and its sustainability. Flood disaster is the crucial issue of the Kathmandu Valley (KV) that devasted the lives of people, property and infrastructures every year in a decade. The rapid growth of unscientific urbanization settlement has been encroached the rivers, river basin and watershed area. So, the Kathmandu valley is in the verge of flood risks. There is enormous challenge to the resilience of river basin community, municipal government, and the sustainability of the Valley.